(untitled) (Fiep Bulletin - online, 2015)
Lateral differences are caused by differences in motor ability, especially strength and coordination. Muscular asymmetry between the legs can lead to mechanical overload and compensatory mechanisms that result in movement and posture changes. Consequences of these lateral differences are higher injury risks and restrictions of sport performance. Therefore the analysis of asymmetries of athletes’ motor behavior is important in order to prevent injuries and to control the recuperation process. The aim of this study was the identification of dynamic lateral differences of the lower limbs. 13 basketball, members of the Brazilian Kadett National Team, and 13 soccer players, members of two professional soccer teams, participated in this study. In order to identify lateral dynamic differences, the athletes performed countermovement jumps on a double force platform. The jump with the best performance was selected for further analyses. The symmetry was identified for maximal force, momentum and maximal power output. Most of the basketball and soccer players (61,5% to 69,2%) are characterized by lateral differences of maximal power output and momentum, but there were no significant differences between the two groups. Concerning the maximal force, only 15,4% of basketball and soccer players are characterized by lateral differences. Although the major physical demands of basketball players are characterized by lateral movements and landings after jumps, the basketball players are dribbling the ball for a good deal of the time. In contrast the soccer players demand basically the lower limbs for shooting, running and vertical jumps. These facts show that jumps are different specific demands according to the sport. However, the different physical demands of soccer and basketball do not result in different lateral dynamic differences.